The Effectiveness of Booklets and Animation Videos on Increasing the Danger of Post Partum Signs Knowledge on the Husband - Wahyu Karyaningtyas; Listyaning Eko Martanti; Erna Widyastuti (Journal of Midwifery Science: Basic and Applied Research, 2020)
The success of health education in the society, depends on the learning component. Attractive media will provide confidence, so the cognitive changes of affection and psychomotor can be accelerated (Siti Zulaekah, 2013). Print media that can be used in the EIC program for the postpartum mother family is a pocket book or booklet (Notoatmodjo, 2012). Audiovisual is one of the media that provide information or messages in audio and visual (Setiawati and Dermawan, 2008). The purpose of this research is to know the effectiveness of the booklet and video animation towards the increasing of puerperal sign knowledge on the husband. This research was conducted in Gayamsari Polyclinic. The type of this research is experimental research, research method in the form of quasi experiment using control group design pretest posttest design. The research population is the husband of postpartum mother period March-April 2018 and the sample was 30 respondents. The Sampling technique by using the purposive sampling, the group determination by using simple random technique (drawing technique). The result of this research using Mann Whitney with Sig 0,268 0,05, mean of control group with booklet was 17,27 higher than intervention group with videos animation, so booklet more effective to increase knowledge husband than used videos animation. The explanation of health education can use a variety of media such as animated videos. Health workers may also actively involve the role of the husbands of the puerperal mother in performing care for the puerperal mother.